Treatment of Chronic Patellar Tendinopathy with Autologous Bone Marrow Stem Cells: A 5-Year-Followup - Cecilia Pascual-Garrido; A. Rolón; A. Makino (Stem Cells International)
The purpose of this study is to determine if patients with chronic patellar tendinopathy will improve clinically after the inoculation of bone marrow mononuclear cells (BM-MNCs). Eight patients with chronic patellar tendinopathy were included. Patients averaged 24 years old (range 14–35). All patients were refractory to conservative treatment for at least 6 months before the procedure. BM-MNCs were harvested from the iliac bone crest and inoculated under ultrasound guide in the patellar tendon lesion. Improvement was assessed through established clinical scores and ultrasound. At 5-year followup, statistically significant improvement was seen for most clinical scores. Seven of eight patients said they would have the procedure again if they had the same problem in the opposite knee and were completely satisfied with the procedure. Seven of 8 patients thought that the results of the procedure were excellent. According to our results, inoculation of BM-MNCs could be considered as a potential therapy for those patients with chronic patellar tendinopathy refractory to nonoperative treatments.